TINJAUAN FILOSOFIS TENTANG KURIKULUM PENDIDIKAN ISLAM (STUDI ANALISIS TERHADAP PEMIKIRAN AL-SYAIBANY) - Ahmad Sukri Harahap (Hikmah, 2019)
In general, the objectives of the Islamic education curriculum are in line with the goals of Islamic education itself, namely guiding humans so that they understand the purpose, functions, and tasks that God created as Humans. The purpose of man is created to know the khaliq, its function is to serve or worship Allah, while his duty is to become khalifa on the earth of Allah. The curriculum has a vital urgency in the implementation of education. Al-Syaibany explained that the curriculum as a tool to support the success of students, the curriculum will be a reference for the success of children in the future. The curriculum also acts as a path that must be taken by all who are related, both students, teachers, principals and others. Without a path, hope, and aspirations in the future are merely wishful thinking. To realize the ideal curriculum, curriculum formators are not enough to base their formulation on only existing problems, but formators need to explore their philosophical foundations.